Immune-mediated liver disease - Heathcote, Jenny (Henry Stewart Talks, 2011)
Diagnosis of Autoimmune Liver Disease (AILD), Diagnosis of Autoimmune Hepatitis (AIH), Steps in management of AIH, AIH treatment, Response to immunosuppressive therapy in AIH, Monitoring during IST for AIH, Remission following therapy in AIH, Presenting features of primary & secondary Sclerosing Cholangitis (PSC), Ulcerative colitis: link to PSC, PSC with Inflammatory Bowel Disease (IBD), Causes of death in PSC, PSC treatment, Medical therapy failure in PSC, Typical presentation of Primary Biliary Cirrhosis (PBC), Liver transplant in PBC vs. PSC, Survival in PBC, Treatment response and histological change in PBC, Complications of PBC